LOOSELY CULTIVATING DISCIPLINE: FROM ZERO TOLERANCE TO PROGRESSIVE DISCIPLINE IN AN ONTARIO SCHOOL BOARD - Milne, Emily (My University, 2011)
This study explores connections between school discipline policies and educational inequality by examining the implementation of “Progressive Discipline” (PD) in an Ontario school board. By using positive reinforcements, preventions, and early and ongoing interventions, PD has replaced more punitive “zero tolerance” approaches as the official approach to student discipline in provincial public schools. This study poses two broad research questions that are guided by prominent theories of school organization and family-school relations: i) Given prevailing schooling practices, how is PD actually implemented, ii) can PD compensate for student inequalities in exposure to cultural orientations demanded by schools. To address these questions, this study draws on 36 qualitative interviews with key actors in several schools, and has two key findings. First, despite the official shift from zero tolerance to PD, student discipline continues to be managed by schools and individual school-based actors along a continuum, with some becoming more progressive, while others remaining more punitive. Thus, this policy evolution has involved a shift from a tighter to a more “loosely coupled” form of organization. But despite this variation, school-based actors are gradually embracing PD, since more progressive perspectives on student discipline appear to resonate with many educators and administrators. Second, the shift to PD is creating new forms of cultural practices in schools, and these practices are generating considerable variations in the outcomes of discipline processes. Building on these findings, this study concludes that progressive discipline policy has the potential to serve as a mechanism of “cultural mobility” and partially compensate for students’ unequal exposure to the values, behaviours and skill sets that are needed to comply with schools’ standards of behaviour.
Keywords: Education; Inequality; Policy; Cultural Capital Theory; Organizational Theory; Educational Assessment, Evaluation, and Research; Educational Assessment, Evaluation, and Research